Measuring the Resilience of Indonesian Islamic Bank Through the RGEC Model - Azhar, Iqlima; Rizka (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
The purpose of this study is to assess the health of Islamic commercial banks using the RGEC technique, which comprises Risk Profile, Good Corporate Governance, Earnings (Rentability), and Capital. Methods of this study employ a quantitative approach based on secondary data from Islamic Commercial Bank financial reports spanning 2015-2024. In this study, descriptive analysis with the RGEC approach was utilized to determine the health of banks. According to the study's findings, the health of Islamic Commercial Banks from 2015 to 2024 has a composite rating of 1 (PK - 1), placing them in the "Very Healthy" category. The NPF ratio is used to analyze the health of Islamic Commercial Banks for the 2015-2024 period, and it ranks one in the extremely healthy group. The assessment of the health level of Islamic Commercial Banks for the period 2015-2024 on the GCG (Good Corporate Governance) aspect using the Self Assessment ratio places them second in the healthy category. The ROA ratio is used to analyze the health of Islamic Commercial Banks for the period 2015-2024 on the Earning (Profitability) component, and it ranks 1 in the very healthy category. The CAR ratio is used to analyze the capital adequacy health of Islamic commercial banks for the period 2015-2024, and it ranks 1 in the extremely healthy category. Implication of this research is that Islamic banks can be categorized as "very healthy" in the 2015-2024 period, thus supporting the theory that the Islamic-based financial system has high resilience to the economic pressure.